2024
DOI: 10.1136/bjsports-2023-106934
|View full text |Cite
|
Sign up to set email alerts
|

Coaches of youth field sports as delivery agents of injury prevention programmes: how are we training the trainers? A scoping review

Lauren Guilfoyle,
Ian C Kenny,
Kieran O'Sullivan
et al.

Abstract: ObjectiveTo systematically map the coach education (CE) component of injury prevention programmes (IPPs) for youth field sports by identifying and synthesising the design, content and facilitation strategies used to address competency drivers and behaviour change.DesignScoping review.Data sourcesPubMed, PsycInfo, EMBASE, CINAHL, SportDiscus and Google Scholar electronic databases were searched using keywords related to IPPs and youth field sports.Eligibility criteria for selecting studiesStudies of IPPs in you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 69 publications
(317 reference statements)
0
0
0
Order By: Relevance
“…This may indicate that while participants knew these were useful, they may not have actually understood why and how these protocols impact injury prevention and, in some cases, simply copied what they may have seen coaches or practitioners do previously. Recent research on injury prevention programmes has also suggested that future research incorporate frameworks that support development of coach competency; however, current challenges of time and finance may limit the feasibility of such strategies without leadership advocacy and support of female coaches in this process ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that while participants knew these were useful, they may not have actually understood why and how these protocols impact injury prevention and, in some cases, simply copied what they may have seen coaches or practitioners do previously. Recent research on injury prevention programmes has also suggested that future research incorporate frameworks that support development of coach competency; however, current challenges of time and finance may limit the feasibility of such strategies without leadership advocacy and support of female coaches in this process ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…These programmes have been effective in reducing non-contact injuries, in particular hamstring strain and overuse injuries ( 21 23 ). Pragmatic barriers (time, cost) often limit coach education towards such interventions to a single day, but effective implementation may be enhanced by future iterations involving greater support and feedback ( 24 , 25 ). The rate at which such interventions are implemented in amateur female sport at present is also unclear ( 19 ).…”
Section: Introductionmentioning
confidence: 99%